Concepts, contents, and consciousness. Issue 1 (5th March 2016) - McClelland, Tom; Bayne, Tim
Abstract: In his paper 'Are we ever aware of concepts? A critical question for the Global Neuronal Workspace, Integrated Information, and Attended Intermediate-Level Representation theories of consciousness' (2015, this journal), Kemmerer defends a conservative account of consciousness, according to which concepts and thoughts do not characterize the contents of consciousness, and then uses that account to argue against both the Global Neuronal Workspace theory of consciousness and Integrated Information Theory of Consciousness, and as a point in favour of Prinz's Attended Intermediate-level Representations theory. We argue that there are a number of respects in which the contrast between conservative and liberal conceptions of the admissible contents of consciousness is more complex than Kemmerer's discussion suggests. We then consider Kemmerer's case for conservatism, arguing that it lumbers liberals with commitments that they need not – and in our view should not – endorse. We also argue that Kemmerer's attempt to use his case for conservatism against the Global Neuronal Workspace and Integrated Information theories of consciousness on the one hand, and as a point in favour of Prinz's Attended Intermediate Representations theory on the other hand, is problematic. Finally, we consider Kemmerer's overall strategy of using an account of the admissible contents of consciousness to evaluate theories of consciousness, and suggest that here too there are complications that Kemmerer's discussion overlooks.